Prototype Aplikasi Cyber Counseling Berbasis Mobile - Dimas Sasongko; Akhmad Liana Amrul Haq; Mukhamad Maftuh Sangiba (Journal of Information System Research (JOSH), 2021)
One of the innovations utilizing the development of Information Technology in counseling services is Cyber Counseling services, often called online counseling. This research aims to prepare a system to support the online counseling process in the form of a mobile application. In this study, we will only discuss the design of applications with a prototype model. This Cyber Counseling mobile application development model is in the process of needs analysis and system design using the prototyping method. This research has produced a prototype of a mobile-based Cyber Counseling Application. The test results using the BlackBox testing method show that the features in the prototype of the Cyber Counseling Application have been running well and can be accepted.